Synthesis of lithium intercalation oxides based manganese and copper by the sol-gel method - Yahya, Rosiyah; Yahya, A.H.; Basirun, Wan Jefrey; Puteh, R.; Arof, Abdul Kariem; Yahya, M.Z.A.; Vengidason, S. (2005)
The current generation of lithium-ion batteries uses LiCoO2 or LiNiO2 as cathodes. In contrast to LiCoO2 and LiNiO2 systems, it is easy to synthesize a Mn-based cathode that contains more than one Li per formula unit. LiCuO2 is also a promising electrode material for lithium batteries and it seems to be an attractive candidate as a new electrode material. LiCoO2 and graphite have layered structures and LiMn2O4 has a tunnel-like framework and both structures are useful for the insertion and de-insertion of lithium guest ions into host materials with minimal physical alteration of the host structure. Therefore, in this work attempts have been made to mix both transition metals of copper and manganese to form mixed Lithium manganese copper oxide as cathodic materials for lithium batteries, and the lithiated intercalation cathode materials (LiM2O4, M=Mn, Cu) were synthesized by the sol gel method. The elements, Mn and Cu were chosen because a Mn-based cathode can easily accommodate more than one lithium per formula unit while Cu has an advantage of lower cost and safety. Various ratios of Mn and Cu acetates, lithium hydroxides were used as starting materials with tartaric acid as the gelating agent. The dried samples were calcined at 800 oC. Structural changes were observed when Cu was introduced into LiMn2O4. Mixed oxides of Li2MnxCuyOz were formed. The structure of the calcined materials was characterized by XRD, EDX and SEM. The XRD patterns for LiM2O4